Moisture in hemodialysis catheter dressings and the risk of infection: an integrative review - Maia, Sayonnara Ferreira; Lira, Jefferson Abraão Caetano; Nogueira, Lidya Tolstenko; Santos, Ana Maria Ribeiro dos; Avelino, Fernanda Valéria Silva Dantas; Silva, Grazielle Roberta Freitas da (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: In hemodialysis care, the nurse is involved in most care for the patient using a double-lumen central venous catheter; in this regard, it is necessary to instruct the renal patient about measures to protect venous access regarding humidity during bathing, as a wet dressing over the device insertion site increases the risk of infection. Aim: To identify in the literature the relationship between moisture in hemodialysis catheter dressings and the risk of infection. Outlining: Integrative review performed in MEDLINE databases via PubMed, CINAHL, Web of Science, Scopus, Cochrane, BDENF, LILACS bibliographic index and references of the articles included. The sample consisted of 10 primary studies. The results were analyzed descriptively and organized into categories. Results: Six (60%) addressed the humidity related to the bath, three (30%) addressed the humidity related to perspiration and one (10%) discussed the humidity related to secretions from the ostium of the hemodialysis catheter. Implications: Wetting the hemodialysis catheter while bathing is not the best recommendation. Moisture resulting from perspiration was associated with risk of infection.